Attracting foreign investments: the path to recovery and development of Ukraine's wood processing industry - Nevar, Oksana; Невар, Оксана (Вежа-Друк, 2023)
Ukraineʼs wood processing industry plays a significant role in the countryʼs economic development and ensures sustainable growth. It contributes to job creation, the production of competitive goods, and the export of products. Additionally, this sector has substantial potential for preserving natural resources and reducing its negative impact on the environment.
Залучення іноземних інвестицій: шлях до відновлення та розвитку деревообробної промисловості України
Деревообробна промисловість України відіграє значну роль в економічному розвитку країни та забезпечує стабільне зростання. Це сприяє створенню робочих місць, виробництву конкурентоспроможної продукції, експорту продукції. Крім того, ця галузь має значний потенціал для збереження природних ресурсів та зменшення їх негативного впливу на довкілля.
Keywords: wood processing industry; economic development; sustainable growth; recovery; 674:338.24(477)